(untitled) (FishTaxa - Journal of Fish Taxonomy, 2022)
The diversity of freshwater fish in the Indo-Nepal transboundary river is minimally known to the common people. The present study adopted an integrated approach to determine the genetic diversity of fish fauna from the river Gandak. We generated 59 DNA barcodes of 25 fish species, identified through meristic and morphometric characters. The studied species revealed monophyletic clustering in the BA topology with high posterior probability supports and sufficient genetic distances. The study hinted more rigorous sampling and development of DNA data are required to develop a robust barcode library for indigenous fishes of Gandak River. A similar attempt will be useful to detect the extant fish diversity of other transboundary riverine systems in India and abroad and assist in reassessing the checklist and encourage sustainable conservation direction to protect the faunal composition in a riverine ecosystem.